Giant brachial pseudoaneurysm secondary to a fish bite injury, a case report - Julián David Moreno Cavanzo; Laura Navarro-Martinez; Alejandro Rojas-Urrea; Daniela Arias-Mariño; Julio Cesar Velasco-Castro; Lorena García-Agudelo (Folia Medica)
Vascular trauma is a frequent reason for consultation in the emergency department and should be addressed systematically; it can compromise the hemodynamic status of the patient. Here we report an uncommon case of a pseudoaneurysm caused by the bite of a river fish named Payara (Hydrolycus scomberoides), which necessitated multidisciplinary clinical and surgical management. Pseudoaneurysm can be caused either by blunt or penetrating trauma; if not properly managed, it can be a life-threatening condition and lead to thrombosis or gangrene, amputation and even death.